2016
DOI: 10.3168/jds.2015-10440
|View full text |Cite
|
Sign up to set email alerts
|

Influence of adipocyte size and adipose depot on the in vitro lipolytic activity and insulin sensitivity of adipose tissue in dairy cows at the end of the dry period

Abstract: The aim of the present research was to describe characteristics of adipose tissue lipolysis in dairy cows with a variable body condition score (BCS). Ten clinically healthy Holstein Friesian cows were selected based on BCS and euthanized 10 to 13 d before the expected parturition date. Immediately after euthanasia, adipose tissue samples were collected from subcutaneous and omental fat depots. In both depots, we observed an increase in adipocyte size with increasing BCS. Using an in vitro explant culture of su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 33 publications
3
42
0
Order By: Relevance
“…This has implications for the management of cows using extended lactations; for example, Delany et al (2010) demonstrated that cows fed in excess of their requirements (in the form of a TMR) gained excess body condition and were unable to sustain milk production to 670 d, unlike their pasture-based counterparts that were able to continue milking. There may also have been variable mobilization of visceral versus subcutaneous fat depots (De Koster et al, 2016). Evidence suggests differential mobilization of adipose stores from visceral and subcutaneous tissues in lactating and nonlactating cows (Hostens et al, 2012;Drackley et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This has implications for the management of cows using extended lactations; for example, Delany et al (2010) demonstrated that cows fed in excess of their requirements (in the form of a TMR) gained excess body condition and were unable to sustain milk production to 670 d, unlike their pasture-based counterparts that were able to continue milking. There may also have been variable mobilization of visceral versus subcutaneous fat depots (De Koster et al, 2016). Evidence suggests differential mobilization of adipose stores from visceral and subcutaneous tissues in lactating and nonlactating cows (Hostens et al, 2012;Drackley et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests differential mobilization of adipose stores from visceral and subcutaneous tissues in lactating and nonlactating cows (Hostens et al, 2012;Drackley et al, 2014). Further, over-conditioned cows are predisposed to excessive mobilization of body fat (De Koster et al, 2016). In light of this, farmers and herd managers will need to be aware of the body condition of cows managed for extended lactations and avoid over-feeding to avoid excess fatness.…”
Section: Discussionmentioning
confidence: 99%
“…When FFA concentrations decrease afterward, ATM remain in AT to fulfill their function. Serum FFA concentration reflects the mobilization of fat from all adipose depots and this may differ between different adipose depot locations (De Koster et al, 2016). Possibly, the infiltration of ATM may be more related to the local release of adipokines and FFA within different adipose depots.…”
mentioning
confidence: 99%
“…In response to lipolysis induced by NEB in late-lactation cows, TNFA gene expression was upregulated; however, no changes were observed in the transcription of other pro-inflammatory cytokines, including IL6 and CCL2 (Contreras et al, 2016). In over-conditioned nonlactating, nongestating cows (i.e., animals with higher basal lipolysis rate; De Koster et al, 2016), the expression of IL1B (encoding IL-1β), CCL2, and IL6 and its receptor (IL6R) is upregulated, especially in visceral AT (Ji et al, 2014). Zachut (2015) characterized the AT proteome in transition cows with intense and moderate lipolysis rates at 17 d before and 4 d after parturition.…”
Section: At Inflammatory Responsementioning
confidence: 99%
“…Other factors that can be hypothesized to contribute in excessive lipolysis of cows overfed during the dry period are the greater amount of adipose mass, as overfed cows will accumulate excess energy in their adipose depots , higher expression of ATGL (Ji et al, 2012), and an increase in adipocyte size. Larger adipocytes have higher levels of basal and stimulated lipolytic activity (De Koster et al, 2016). The current recommended strategy to feed cows during the dry period, in view of limiting lipolysis, is to meet but not exceed energy requirements while maximizing DMI.…”
Section: Prepartum Energymentioning
confidence: 99%